2014
DOI: 10.1111/jmwh.12146
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Skills Retention Among Frontline Health Workers: Community Maternal and Newborn Health Training in Rural Ethiopia

Abstract: Introduction We examined the degree to which the skills and knowledge of health workers in Ethiopia were retained 18 months after initial maternal and newborn health training and sought to identify factors associated with 18‐month skills assessment performance. Methods A nonexperimental, descriptive design was employed to assess 18‐month skills performance on the topics of Prevent Problems Before Baby Is Born and Prevent Problems After Baby Is Born. Assessment was conducted by project personnel who also receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 30 publications
7
46
1
Order By: Relevance
“…Ten (22.2%) of the 45 studies reported a breakdown of scores according to cadre, 26,36,39,40,44,50,53,55,56,74 and 7 (70.0%) of these studies showed that birth attendants from lower cadres (eg, midwives) improved significantly more from pretraining to posttraining than those from higher cadres (eg, physicians). 26,40,42,50,53,56,74 In all 7 of these studies, significant differences in pretraining test performance between different cadres were diminished or completely eliminated upon retesting after training.…”
Section: Association Between Birth Attendant Characteristics and Acqumentioning
confidence: 99%
See 4 more Smart Citations
“…Ten (22.2%) of the 45 studies reported a breakdown of scores according to cadre, 26,36,39,40,44,50,53,55,56,74 and 7 (70.0%) of these studies showed that birth attendants from lower cadres (eg, midwives) improved significantly more from pretraining to posttraining than those from higher cadres (eg, physicians). 26,40,42,50,53,56,74 In all 7 of these studies, significant differences in pretraining test performance between different cadres were diminished or completely eliminated upon retesting after training.…”
Section: Association Between Birth Attendant Characteristics and Acqumentioning
confidence: 99%
“…41,52,55,67 Furthermore, 4 (80%) of the 5 studies showing no falloff or mixed results featured refresher training or regular meetings to reinforce material learned. 43,52,55,67 Two of the studies with refresher courses showed an actual increase in knowledge and skills at 1 year and 18 months after training, respectively, compared with immediately after training. 52 Of note, the 2 educational interventions from Ethiopia provided refresher training, but they also sought to educate women in the community and increase their demand for skilled maternal and newborn care, which may have been an important incentive for birth attendants to maintain their knowledge and skills.…”
Section: Retention Of Knowledge and Skillsmentioning
confidence: 99%
See 3 more Smart Citations